2019
DOI: 10.2147/cmar.s186432
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of preoperative exercise therapy on surgical outcomes in lung cancer patients with or without COPD: a systematic review and meta-analysis</p>

Abstract: Objectives This meta-analysis aimed to demonstrate the impact of preoperative exercise therapy on surgical outcomes in patients with lung cancer and COPD. Pulmonary function and muscle capacity were investigated to explore their potential links with outcome improvements after exercise. Methods Articles were searched from PubMed, Embase, and the Cochrane Library with criteria of lung cancer patients with or without COPD, undergoing resection, and receiving preoperative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
2
27
1
Order By: Relevance
“…Our ndings of very low-quality evidence about the effects of prehabilitation programs for HRQoL align with those reported by seven systematic reviews published recently(47, 49, 54-56, 59, 60).Contradictory ndings in different HRQoL domains have been reported by other systematic reviews (46, 48, 50, 53, 58, 61). Similarly, our ndings of very low certainty in the effects of prehabilitation programs to reduce postoperative complications coincide with those of low certainty reported by Xiang Li and colleagues in 2016(57). Other systematic reviews have reported signi cant reductions in this outcome(47-49, 51-54, 58, 61, 62) A similar trend is observed in the literature about other outcome measures in this review.…”
supporting
confidence: 90%
“…Our ndings of very low-quality evidence about the effects of prehabilitation programs for HRQoL align with those reported by seven systematic reviews published recently(47, 49, 54-56, 59, 60).Contradictory ndings in different HRQoL domains have been reported by other systematic reviews (46, 48, 50, 53, 58, 61). Similarly, our ndings of very low certainty in the effects of prehabilitation programs to reduce postoperative complications coincide with those of low certainty reported by Xiang Li and colleagues in 2016(57). Other systematic reviews have reported signi cant reductions in this outcome(47-49, 51-54, 58, 61, 62) A similar trend is observed in the literature about other outcome measures in this review.…”
supporting
confidence: 90%
“…A meta-analysis performed by Li et al included three randomised controlled trials looking at PPCs in those with COPD and lung cancer. Whilst there was an overall reduction in length of stay, there was only a trend to a reduction in PPCs, that did not reach statistical significance, however numbers were small [ 51 ]. We believe it would be reasonable to recommend exercise therapy prior to surgery if this does not delay surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies had supported the positive roles of rehabilitation in decreasing postoperative complications and mortality, but the majority of them are based on a single center and a limited number of patients, and they thus could not avoid selection bias. The latest systemic analysis was published in 2019 and only enrolled publications before June 2017 ( 21 ). We therefore conducted this study to update the records and explore the clinical value of pulmonary rehabilitation in decreasing postoperative complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies only included a randomized controlled trial (RCT) for future calculation ( 22 ). In addition, the newest one was published in 2019, and it only enrolled the publications before June 2017 ( 21 ). In the last few years, some new pulmonary rehabilitation clinical trials have been reported, including some non-RCT trials.…”
mentioning
confidence: 99%